KNOWLEDGE BASES FOR DIFFERENT ARTIFICIAL INTELLIGENCE METHODS USED IN TRANSPORTATION SYSTEMS - Киркина, Татьяна; Киркин, Александр (SWorldJournal, 2021)
The development of the methodology for the intellectualization of various systems has led to the identification of many effective methods for solving the problems of creating and functioning of intelligent systems, and at the same time has expanded the ar